Two noveland simple correlations to estimate equilibrium water dew point for natural gas dehydration process - Benitez, Leonel Alberto (2014)
Water is probably the most undesirable component found in crude natural gas because its presence can produce hydrate formation, and it can also lead to corrosion or erosion problems in pipes and equipment. Natural gas must be dehydrated before being transported through a long distance to ensure an efficient and trouble-free operation. Thermodynamic modelling of triethyleneglycol (TEG)-water system is still rather inaccurate, especially with regard to systems at high temperature and high TEG concentration. As a consequence, design and operation of absorber towers are affected by the lack of accurate data. Two novel correlations have been developed to estimate the equilibrium water dew point of a natural gas stream by evaluating experimental data and literature. These data were collected and analyzed by means of images scanned with MATLAB software R2012B version. An average percentage error is of 1-2% for linear correlation and it is of 2-3% for non-linear correlation. Results are quite accurate and they are consistent with literature data. Due to the simplicity and precision of the correlations developed in this work, the equations obtained have a great practical value. Consequently, they allow process engineers to perform a quick check of the water dew point at different conditions without using complex expressions or graphics.